PENTINGNYA PENDIDIKAN SEKSUAL DI REMAJA SMP - Muhammad Naufal Fajar; Benggol Sang Ghany; Muhammad Iqmal Abdullah (CV. ADIBA AISHA AMIRA, 2025)
Sexual education is an integral aspect of individual development that cannot be ignored, especially at the adolescent stage at junior high school (SMP) level. During this period, teenagers experience significant physical, emotional and social changes, so it is important to provide a comprehensive understanding of aspects of sexuality. Sexual education at the junior high school level has a crucial role in forming a healthy, positive and ethical understanding of sexual identity, interpersonal relationships and responsibility as an individual. This learning is not only limited to biological aspects, but also involves moral values, social norms and interpersonal skills which are essential for the holistic development of students. The research methods used in the process of collecting data and information are literature studies and surveys. This method is used. Most sexual education research at the junior high school level begins with a literature study to understand trends, theories and previous findings. Searching for data was carried out using the survey method. This method may include structured questions to measure their understanding of certain topics, perceptions of sexual education, and its impact on attitudes and behavior. systematically to be able to describe, explain and understand activities or events that occurred some time ago. Adolescence is synonymous with a period of preservation that is closely related to the tendency to show oneself, feeling autonomous over oneself, searching for one's identity, and other risky behavior. Adolescents' exploration of themselves and various things outside themselves is of course normal as long as it is within certain limits. Therefore, sexuality education to teenagers is mandatory. However, sexuality education is often considered taboo.